Illness presenteeism among physicians and trainees: Study protocol of a scoping review. - Lorenzo Madrazo; Jade Choo-Foo; Marie-Cécile Domecq; Kori A LaDonna; Susan Humphrey-Murto (PLoS ONE, 2024)
Background Illness presenteeism (IP) is the phenomenon where individuals continue to work despite illness. While it has been a prevalent and longstanding issue in medicine, the recent onset of the COVID-19 pandemic and the growing movement to improve physician wellness brings renewed interest in this topic. However, there have been no comprehensive reviews on the state of literature of this topic. Purpose The main aim of this scoping review is to explore what is known about presenteeism in physicians, residents, and medical students in order to map and summarize the literature, identify research gaps and inform future research. More specifically: How has illness presenteeism been defined, problematized or perceived? What methods and approaches have been used to study the phenomenon? Has the literature changed since the pandemic? Method Using the Arksey and O'Malley framework several databases will be searched by an experienced librarian. Through an iterative process, inclusion and exclusion criteria will be developed and a data extraction form refined. Data will be analyzed using quantitative and qualitative content analyses. Potential implications of results By summarizing the literature on IP, this study will provide a better understanding of the IP phenomena to inform future research and potentially have implications for physician wellness and public health.